KEWASPADAAN UNIVERSAL PELAYANAN KESEHATAN GIGI DI PUSKESMAS SE-KABUPATEN BANYUMAS - Fani Tuti Handayani; A. Haris Budi Widodo (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2010)
ABSTRACT In the past last years, universal precaution have been introduced by The Ministry of Health, Republic of Indonesia. The sosialization of universal precaution were function as an efforts on blood and body fluids infection control. Dental treatment procedures may cause any blood and body fluids that enable become an infecting agent. This research purpose was to determine the application of universal precaution on dental treatment prosedures in the public health center (Puskesmas) in the regency of Banyumas as an efforts on blood and body fluids infection control. This is a descriptive survey research. Sample in this research were total of the population constitude 39 public health center in the regency of Banyumas. The method used to collect data was interview with questionnaire sheets. An univariate analysis was used to analyze all data by SPSS computer program version 16 for windows. The result of this research shows 25,6% of dental polyclinic at public health center in the regency of Banyumas were categorized as good in management of the needle or sharp applience perfectly. 38,5 % of dental polyclinic at public health center in the regency of Banyumas decontaminate all health appliances. 59 % of dental polyclinic at public health center in the regency of Banyumas were categorized as good in hand washing to prevent the cross infection. The application of perfect protection for blood exposure was 0%. 87,2% of dental polyclinic at public health center in the regency of Banyumas do waste disposal properly and safety. Key Words : Universal precaution, dental health, public health center. Kesmasindo Volume 3, Nomor 1, Januari 2010, hlm. 47-55